Sisyphe. - Ferro, Francisco. (2017)
Abstract: Sisyphe, a work written between June and September 2010, calls for a sextet (flute, Bb clarinet, violin, cello, percussion and piano) and has an approximate duration of eleven minutes. My desire to write for the so-called "Pierrot" ensemble stems from practical reasons, as many groups that are called "new music ensembles" have this set of instruments as their core. In this thesis, Sisyphe will be assessed in terms of both general aesthetic viewpoints and specific compositional techniques. The short reflections on topics such as form and creative process will contribute to a better understanding of my attitude towards the act of composing as well as my creative intentions.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Music.; Advisor: John McDonald.; Committee: Janet Schmalfeldt, and Alessandra Campana.; Keyword: Music.